Persistence of Internal Representations of Alternative Voluntary Actions - Filevich, Elisa; Haggard, Patrick (Frontiers in Psychology, 2013)
We have investigated a situation in which externally available response alternatives and their internal representations could be dissociated, by suddenly removing some action alternatives from the response space during the interval between the free selection and the execution of a voluntary action. Choice reaction times in this situation were related to the number of initially available response alternatives, rather than to the number of alternatives available effectively available after the change in the external environment. The internal representations of response alternatives appeared to persist after external changes actually made the corresponding action unavailable. This suggests a surprising dynamics of voluntary action representations: counterfactual response alternatives persist, and may even be actively maintained, even when they are not available in reality. Our results highlight a representational basis for the counterfactual course of action. Such representations may play a key role in feelings of regret, disappointment or frustration. These feelings all involve persistent representation of counterfactual response alternatives that may not actually be available in the environment.